Relationships Between Body Mass Index with Cholelithiasis - Husin Thamrin; Nadieda Ayu Marthalitasari; Subur Prajitno (Universitas Muhammadiyah Surabaya, 2020)
AbstractGallstones formed due to imbalance of bile components, excessive/ high level of cholesterol, nor bilirubin. Obesity was a condition where body mass index (BMI) was excess, which can cause health problems such as an increase of cholesterol, triglycerides, insulin levels, and blood pressure. There’s growing attention to cholelithiasis in Indonesia, but there wasn’t any data on the prevalence due to the limited amount of study related to cholelithiasis and BMI. This study aimed to analyze the relationship between BMI and cholelithiasis in Dr. Soetomo General Hospital. An analytical descriptive study with the case-control design was conducted, and the data were collected from medical records. The sample was 124 patients from the internal outpatient clinic Dr. Soetomo General Hospital. The data were analyzed using a t-test 2 independent sample. The ratio between female and male patients was 3:1, mean of age was 36-45 years, 45.2% had weight range from 61-70 kg, 51.2% had height range 150-159 cm, the BMI from patient with cholelithiasis specifically 45.3% on at-risk scale and 40% on obese I, the result showed p-value 0.089 (p>0.05), which means that there was no significant differences with the BMI from patients with cholelithiasis and without cholelithiasis. In conclusion, BMI could not be used as a parameter to determine the occurrence of cholelithiasis on an individual.Keywords: body mass index, cholelithiasis, gallstone